Breast cancer metastasis: immune profiling of lymph nodes reveals exhaustion of effector T cells and immunosuppression. Issue 1 (12th July 2021) - Rye, Inga Hansine; Huse, Kanutte; Josefsson, Sarah E.; Kildal, Wanja; Danielsen, Håvard E.; Schlichting, Ellen; Garred, Øystein; Riis, Margit L.; OSBREAC,; Lingjærde, Ole Christian; Myklebust, June H.; Russnes, Hege G.
Abstract : Sentinel lymph nodes are the first nodes draining the lymph from a breast and could reveal early changes in the host immune system upon dissemination of breast cancer cells. To investigate this, we performed single‐cell immune profiling of lymph nodes with and without metastatic cells. Whereas no significant changes were observed for B‐cell and natural killer (NK)‐cell subsets, metastatic lymph nodes had a significantly increased frequency of CD8 T cells and a skewing toward an effector/memory phenotype of CD4 and CD8 T cells, suggesting an ongoing immune response. Additionally, metastatic lymph nodes had an increased frequency of TIGIT (T‐cell immunoreceptor with Ig and ITIM domains)‐positive T cells with suppressed TCR signaling compared with non‐metastatic nodes, indicating exhaustion of effector T cells, and an increased frequency of regulatory T cells (Tregs) with an activated phenotype. T‐cell alterations correlated with the percentage of metastatic tumor cells, reflecting the presence of metastatic tumor cells driving T effector cells toward exhaustion and promoting immunosuppression by recruitment or increased differentiation toward Tregs. These results show that immune suppression occurs already in early stages of tumor progression. Abstract : Sentinel lymph nodes (SLN) are the first nodes draining the lymph from a breast and could reveal early changes in the host immune system upon dissemination of breast cancer (BC) cells. We used single‐cell mass cytometry and functional analyses of metastatic and non‐metastatic LN and revealed a dysfunctional and suppressed immune response. Metastatic LN had an increased frequency of TIGIT‐positive T cells with suppressed TCR signaling compared with non‐metastatic nodes and an increased frequency of Tregs with an activated phenotype. The alterations were correlated with metastatic tumor burden in the LN of patients with BC.